Conceptual Framework for the Specialized Education System Implementation for Children in the Kaliningrad region - Anna Budarina; Alexandra Zyolko; Margarita Korotkevich; Tatiana Petrova (ARPHA proceedings, 2022)
The article discusses the relevance of the introduction of innovative forms of specialized education for children; it is proposed to get acquainted with the experience of implementing such a project on the basis of the IKBFU. The tasks of the educational project "Star of the Future" are revealed - the integration of general and additional education and future employers in order to expand the possibilities of vocational guidance training for children studying in specialized classes, mastering specialized subjects in various educational forms (modular training, project and online training, work in university laboratories , professional tests at enterprises and organizations), creating conditions for the formation of a child's image of a future profession and its conscious choice. The cluster approach to project implementation is substantiated as a direction in science and practice associated with the search and implementation of new opportunities for the development of society, increasing its welfare and competitiveness through the creation and management of clusters. The features of the project are listed: integration of basic (school part) and additional (university part) education; formation of universal competences, Digital and soft-competencies (including critical thinking, teamwork, communication and others); entrepreneurship training, formation of understanding of the “image of the future and professions of the future”; Deferred contract and targeted training; support and training of teachers who, in partnership with university teachers, implement programs. The quantitative and qualitative results of the project are proposed, the analysis of the effectiveness of the training is carried out for the assessment of which Donald Kirkpatrick`s four-level model was used. A conclusion is made about the success of the project and further ways of its development are discussed.